Impact of SARS-CoV-2 on training and mental well-being of surgical gynecological oncology trainees. Issue 9 (September 2021) - Gaba, Faiza; Blyuss, Oleg; Rodriguez, Isabel; Dilley, James; Wan, Yee-Loi Louise; Saiz, Allison; Razumova, Zoia; Zalewski, Kamil; Nikolova, Tanja; Selcuk, Ilker; Bizzarri, Nicolò; Theofanakis, Charalampos; et al.
Abstract : Introduction: The SARS-CoV-2 global pandemic has caused a crisis disrupting health systems worldwide. While efforts are being made to determine the extent of the disruption, the impact on gynecological oncology trainees/training has not been explored. We conducted an international survey of the impact of SARS-CoV-2 on clinical practice, medical education, and mental well-being of surgical gynecological oncology trainees. Methods: In our cross-sectional study, a customized web-based survey was circulated to surgical gynecological oncology trainees from national/international organizations from May to November 2020. Validated questionnaires assessed mental well-being. The Wilcoxon rank-sum test and Fisher's exact test were used to analyse differences in means and proportions. Multiple linear regression was used to evaluate the effect of variables on psychological/mental well-being outcomes. Outcomes included clinical practice, medical education, anxiety and depression, distress, and mental well-being. Results: A total of 127 trainees from 34 countries responded. Of these, 52% (66/127) were from countries with national training programs (UK/USA/Netherlands/Canada/Australia) and 48% (61/127) from countries with no national training programs. Altogether, 28% (35/125) had suspected/confirmed COVID-19, 28% (35/125) experienced a fall in household income, 20% (18/90) were self-isolated from households, 45% (57/126) had to re-use personal protective equipment, and 22% (28/126) purchased their own. In total, 32.3% (41/127) of trainees (16.6% (11/66) from countries with a national training program vs 49.1% (30/61) from countries with no national training program, p=0.02) perceived they would require additional time to complete their training fellowship. The additional training time anticipated did not differ between trainees from countries with or without national training programs (p=0.11) or trainees at the beginning or end of their fellowship (p=0.12). Surgical exposure was reduced for 50% of trainees. Departmental teaching continued throughout the pandemic for 69% (87/126) of trainees, although at reduced frequency for 16.1% (14/87), and virtually for 88.5% (77/87). Trainees reporting adequate pastoral support (defined as allocation of a dedicated mentor/access to occupational health support services) had better mental well-being with lower levels of anxiety/depression (p=0.02) and distress (p<0.001). Trainees from countries with a national training program experienced higher levels of distress (p=0.01). Mean (SD) pre-pandemic mental well-being scores were significantly higher than post-pandemic scores (8.3 (1.6) vs 7 (1.8); p<0.01). Conclusion: SARS-CoV-2 has negatively impacted the surgical training, household income, and psychological/mental well-being of surgical gynecological oncology trainees. The overall clinical impact was worse for trainees in countries with no national training program than for those in countries with a national training program, although national training program trainees reported greater distress. COVID-19 sickness increased anxiety/depression. The recovery phase must focus on improving mental well-being and addressing lost training opportunities.